Analisa Kinematika Monobike Mechanical Toys Menggunakan GNU Octave dan Solidworks - Eva Hertnacahyani Herraprastanti; Suluh Jatmiko (Politeknik Negeri Padang, 2019)
Industry era 4.0 allows the use of cyber technology, both physical and non-physical, in all aspects of life, including the toy industry. 3-dimensional printers as a key technology industry 4.0 plays an important role. Before it is printed using a 3D printer, it becomes a real product ready to be marketed, first the product is simulated to find out if the toy product can move according to the kinematics that we design. This analysis includes the displacement, velocity, and linear and angular acceleration of the Monobike component. In this research, the analysis of component movements is limited to Link 3. In this study, a toy that can mimic the motion of an object as precisely as possible is determined, which is a monobike toy. Monobike mechanical toys mimic human activities of pedaling a bicycle. The methodology in this research is as follows: 1) Determine the dimensions of the monobike component, 2) Determine the monobike drive components, 3) Make a monobike kinematic diagram, 4) Perform kinematic analysis using the position vector of the monobike component, 5) Perform displacement, velocity calculations , and theoretical acceleration with Excel, 6) Perform kinematic analysis with Solidworks, 7) Comparison of theoretical calculation results and Solidworks simulation results. Based on the results of theoretical research and Solidworks simulations, the values ​​of displacement, velocity and acceleration are close. The average error for linear displacement is 0.261%, linear velocity 0.852%, linear acceleration 0.7664%, angular velocity 0.372%, and angular acceleration 0.492%. Kinematic analysis in monobike mechanical toys theoretically using Excel and simulation with Solidworks software, the results are more or less the same, so it can be said that this research is accurate. Solidworks is recommended as software that can be used to simulate movements in kinematic analysis.